2020
DOI: 10.1038/s41598-020-59732-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of corticosteroids in influenza-associated acute respiratory distress syndrome and severe pneumonia: a systemic review and meta-analysis

Abstract: Influenza-related severe pneumonia and acute respiratory distress syndrome (ARDS) are severe threats to human health. The objective of this study was to assess the effects of systematic corticosteroid therapy in patients with pneumonia or ARDS. The PubMed, EMBASE, Web of Science and SCOPUS databases were searched up to July, 2019. Nineteen studies including 6637 individuals were identified, and fifteen studies (6427 patients) were included in the meta-analysis of mortality. Eighteen were observational studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 41 publications
0
57
1
4
Order By: Relevance
“…Ventilator -free days up to day 28 The 5 trials (in cluding 771 patients) that examined ventilator free days up to day 28 revealed a significant in crease in the mean number of ventilator free days with corticosteroid treatment (MD, 4.28 days; 95% CI, 2.67-5.88; P <0.001; I 2 = 21%; moderate certainty) (FIGURE 3). The MD was 4.28 (95% CI, 2.67-5.88) more ventilator free days (Supple mentary material, Table S2).…”
Section: Duration Of Mechanical Ventilationmentioning
confidence: 99%
“…Ventilator -free days up to day 28 The 5 trials (in cluding 771 patients) that examined ventilator free days up to day 28 revealed a significant in crease in the mean number of ventilator free days with corticosteroid treatment (MD, 4.28 days; 95% CI, 2.67-5.88; P <0.001; I 2 = 21%; moderate certainty) (FIGURE 3). The MD was 4.28 (95% CI, 2.67-5.88) more ventilator free days (Supple mentary material, Table S2).…”
Section: Duration Of Mechanical Ventilationmentioning
confidence: 99%
“…(16,17) Current recommendations advise against corticosteroids for in uenza pneumonia, but in critically ill patients on vasopressors, there is a contrary recommendation to suggest steroids for vasopressor refractory shock. (18,19) Vitamin C has been already used in COVID 19 patients requiring mechanical ventilation and studies are underway looking at the combination of Vitamin C and corticosteroids in COVID-19. (20)…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall evidence scenery, which was mainly influenced by weaker non-randomized observational type studies, was very conflicted. Anyway, a very recent systemic review and meta-analysis on the use of corticosteroids in patients with influenza-related ARDS and severe pneumonia found an association between corticosteroid therapy and increased mortality and incidence of nosocomial infection [ 13 ].…”
Section: Corticosteroidsmentioning
confidence: 99%